Brain Distribution of 10 cart Transcripts and Their Response to 4 Days of Fasting in Atlantic Salmon (Salmo salar L.) - Kalananthan, Tharmini; Gomes, Ana S.; Lai, Floriana; Tolås, Ingvill; Jordal, Ann-Elise O.; Norland, Sissel; Murashita, Koji; Rønnestad, Ivar (Frontiers in Marine Science, 2021)
Cocaine- and amphetamine-regulated transcript (CART) is known to be involved in feeding and energy balance in mammals, acting as an anorexigenic neuropeptide in hypothalamus. In Atlantic salmon, little is known about Cart brain localization and its function. In this study, in silico analysis revealed the existence of ten cart paralogs, here named cart1a, 1b1, 1b2, 2a, 2b1, 2b2, 3a1, 3a2, 3b and 4. The Atlantic salmon Cart sequences shared from 19 to 50% of identity with the human homolog and between 25-90% of sequence identity among paralogs, except for Cart4 which only shared 18-23% of identity. We further explored cart mRNA expressions in 8 brain regions (Olfactory Bulb-OB, Telencephalon-TEL, Midbrain-MB, Cerebellum-CE, Hypothalamus-HYP, Saccus vasculosus-SV, Pituitary-PT and Brain Stem-BS) of Atlantic salmon smolt under 4 days of fasting and continuous fed conditions. The cart paralogs analyzed were widely distributed among brain regions and OB, TEL, HYP, MB and BS seemed to be the major sites of expression. The expression of cart1a and 1b showed quite similar pattern in MB, HYP and BS. The expression of cart2a had the highest in MB followed by HYP and TEL. The cart3a transcript was widely distributed in rostrocaudal regions of brain except in OB and SV whereas cart3b was predominantly expressed in BS followed by MB. Expression of cart4 was high in HYP followed by TEL. With regards to effect of feeding status the Atlantic salmon cart2b, which is the most abundant among the paralogs, was upregulated after 4 days of fasting in OB, MB and HYP compared to fed group. This may suggest an unexpected, but possible orexigenic role of cart2b in Atlantic salmon or a fasting induced stress effect. No other significant effect was observed. Collectively, the differential expressions of the cart paralogs in different brain regions suggest that they may have roles in regional integration of appetite signals and are possibly involved in regulating other brain functions in Atlantic salmon. The fact that salmon has 10 cart paralogs, while mammalians only one, opens interesting perspectives for comparative research on evolutionary adaptations of gene function in the control of appetite and energy homeostasis.